ANALISIS KEPATUHAN WAJIB PAJAK SEBELUM DAN SESUDAH PELAKSANAAN SUNSET POLICY DI BADAN PELAYANAN PAJAK DAERAH KOTA MALANG - Lailatul Ilma Aulia; Afifudin Afifudin; M. Cholid Mawardi (Universitas Islam Malang, 2017)
This study aims to analyze how the impact of sunset policy of taxpayer compliance especially in Badan Pelayanan Pajak Daerah Kota Malang. The data used is the amount of taxpayers and Payer of tax. Data analysis technique used is descriptive analysis. The results have shown the amount of taxpayers and the payer of tax, experience the difference in the form of an increase between before and after sunset policy. Finally it can be conclude that the linkage sunset policy implementation in 2016 and 2017 of taxpayer compliance in Badan Pelayanan Pajak Daerah Kota Malang is influential on taxpayer compliance.